The Influence and Controlling of Industry 4.0 on Work Behavior and Employee Productivity in Start-Up Technology Companies - S. Siregar, Thurman; Nurohmat, Siska Maulina; Khuzaini; Shaddiq, Syahrial; Fahmanadie, Daddy (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
Industry 4.0, with technological advances such as automation, artificial intelligence, and big data, has brought significant changes in the way employees work and productivity in start-up technology companies. This transformation requires employees to develop new skills and adapt to a more dynamic and complex work environment. This research aims to analyze the influence of Industry 4.0 on work behavior and controlling employee productivity through the Systematic Literature Review (SLR). This research uses the Systematic Literature Review (SLR) method to collect and analyze relevant literature regarding the influence of Industry 4.0 on work behavior and employee productivity. Inclusion and exclusion criteria were established to select relevant studies from a variety of sources, including scientific journals, books, industry reports, and other reliable sources. Data were analyzed using a qualitative approach with a focus on identifying main themes from the literature collected. The analysis results show that Industry 4.0 brings significant changes in work behavior, including the need for flexibility and adaptation to new technology. Training and developing digital skills is very important to increase productivity. Transformational leadership has been proven to have a positive impact on employee motivation and performance. Apart from that, effective human resource management and a focus on employee welfare are also key factors in facing the challenges and exploiting the opportunities presented by Industry 4.0. This research concludes that the adoption of Industry 4.0 technology brings many benefits in increasing employee productivity and efficiency, but also demands significant changes in HR management strategies and skills training. Start-up technology companies need to invest in developing digital skills, employ transformational leadership, and create work environments that support employee well-being to maximize the benefits of this transformation. These findings provide valuable insights for companies looking to optimize employee productivity in this digital era.